(3GOGQI GdehGQO GdHTQjIs - (3eUWai eUWai(B, (3cGeds ((3GdbGgQI(B:s (3GdTQcI GdYQHjI ddfTQ hGdJhRjY(B,s, 1994)
(3aj gPG GdcJGH (B: (3eONd eaGgej (B. (3GdJMdjd GdJfXjej , GdSdhc GdJfXjej YdGbGJ GdYed (B:(3GdUQGY hGdJZjjQ , GOGQI GdCaQGO GdYdGbGJ GdUfGYjIs
Keywords: (3GOGQIs; (3GdCaQGOs; (3ehGQO HTQjIs